2007
DOI: 10.1039/b700368d
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of individual human mesenchymal stem cells probed by FTIR microscopic imaging

Abstract: Objective of this study is the novel application of Fourier transform infrared (FTIR) microscopic imaging to identify the differentiation state of individual human mesenchymal stem cells with or without osteogenic stimulation. IR spectra of several hundred single cells with lateral resolution of 5-10 microm were recorded using a FTIR imaging spectrometer coupled to a microscope with a focal plane array detector. A classification model based on linear discriminant analysis was trained to distinguish four cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 26 publications
5
55
0
Order By: Relevance
“…Fourier transform infrared (FTIR) microscopic imaging of human mesenchymal stem cells (hMSCs), furthermore, shows extensive areas of peripheral glycogen accumulation in some cells. [36] The present results also complement the observation that linear discriminant analysis differentiates FTIR spectra of unstimulated hMSCs (apparently fixed within 24 h of passaging) into groups with either high or low peripheral glycogen accumulation [36] and support the electron microscopic observations of an abundant cytoplasmic glycogen content in hESCs. [26] …”
Section: Resultssupporting
confidence: 73%
“…Fourier transform infrared (FTIR) microscopic imaging of human mesenchymal stem cells (hMSCs), furthermore, shows extensive areas of peripheral glycogen accumulation in some cells. [36] The present results also complement the observation that linear discriminant analysis differentiates FTIR spectra of unstimulated hMSCs (apparently fixed within 24 h of passaging) into groups with either high or low peripheral glycogen accumulation [36] and support the electron microscopic observations of an abundant cytoplasmic glycogen content in hESCs. [26] …”
Section: Resultssupporting
confidence: 73%
“…This technique is very rapid, non-destructive and non-invasive for the sample, and does not require special time consuming sample preparation. Recently a few publications have started to appear in the lit- erature reporting the use of FTIR spectroscopy to study a number of different stem cell types e.g., murine embryonic stem cells [21], human corneal stem cells [22], human mesenchymal stem cells [23] and cardiac stem cell [24]. This is the first study to our knowledge which has reported FTIR spectroscopic changes in mESCs undergoing differentiation towards neural lines.…”
Section: Introductionmentioning
confidence: 92%
“…Human mesenchymal stem cells (hMSCs) with and without osteogenic stimulation were also characterized by IR spectroscopy to identify FTIR signatures of their differentiation state [37]. FTIR microscopic images of individual hMSCs that were fixed and dried on calcium fluoride slides were obtained using an FTIR microscope equipped with an FPA detector.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%